2014
DOI: 10.1021/jp504551v
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of Conductivity and Density of States of NiO Mesoporous Films Used in p-Type DSSCs

Abstract: Nickel oxide has been used as the mesoporous electrode material for p-type dye sensitized solar cell (DSSC) for many years, but no high efficiency cells have been obtained yet. The poor results are commonly attributed to the lack of conductivity of the NiO film. In this paper we studied the electrical conduction of NiO mesoporous film with cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). We used unsensitized NiO on FTO as an electrode with no dye adsorbed on the surface. Tests made wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 37 publications
4
94
0
Order By: Relevance
“…For example, Huang et al reported that g of NiO p-DSSCs will enhance by 146 %, if the interface recombination can be artificially eliminated [11]. This serious interface recombination of p-type DSSCs is mainly attributed to two factors: firstly, the position of the NiO valence band is close to the I 3 -/I -redox potential and would cause an overlap between them [2][3][4], and secondly there are trap states placed slightly above the valence band widely that act as carrier generation-recombination centers at the NiO/ dye/electrolyte interface [12,13]. Obviously, the adjustment of suitable band energetic structure and elimination or passivation of surface trap states can provide an effective way to reduce the recombination losses in p-type DSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Huang et al reported that g of NiO p-DSSCs will enhance by 146 %, if the interface recombination can be artificially eliminated [11]. This serious interface recombination of p-type DSSCs is mainly attributed to two factors: firstly, the position of the NiO valence band is close to the I 3 -/I -redox potential and would cause an overlap between them [2][3][4], and secondly there are trap states placed slightly above the valence band widely that act as carrier generation-recombination centers at the NiO/ dye/electrolyte interface [12,13]. Obviously, the adjustment of suitable band energetic structure and elimination or passivation of surface trap states can provide an effective way to reduce the recombination losses in p-type DSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…MgO/NiO samples the peak frequency of the diffusion resistance (around 5 Hz) remains unchanged as the applied potential increases, but the shift of the peak frequency of the charge transfer resistance as the applied potential increases is indicative of a faster interfacial reaction rate. 4 This decreases with increasing concentration of MgO, until it is almost negligible for the 25% wt. MgO/NiO sample.…”
Section: Electrochemical Propertiesmentioning
confidence: 94%
“…This behavior agrees with that reported by D'Amario and co-workers. 4 As the amount of Mg in the films increases this middle peak increases in size; for 0-5% wt.…”
Section: Electrochemical Propertiesmentioning
confidence: 97%
“…This suggests that as ΔGreg is reduced, so should be the driving force for recombination between the dye anion and the injected hole, furthermore, D'Amario et al recently demonstrated deep traps in NiO [179]. In spite of this and low conductivity in bulk NiO, mesoporous NiO appears to be capable of supporting high photocurrents (in the range of 20 mA/cm 2 , which is what would be required of a high performance pnDSC.…”
Section: Decreasing Recombination / Increasing the Fill Factormentioning
confidence: 99%